O fio da violência conjugal nas narrativas de Mia Couto - Aline Teixeira da Silva Lima (Revista Odisséia, 2023)
Regardless of its guise, gender violence exposes the social imbalance of society, demonstrating the relationship of power and domination of men and submission of women. In this way, the objective of this article is to analyze the representation of the conjugal violence in contemporary literature, through the analysis of the short stories "Os olhos dos mortos" and "Meia culpa, meia própria culpa", which make up the book O fio das miçangas (2004), by the Mozambican writer Mia Couto. Furthermore, we seek to understand and problematize the representation of the pain of the other and the positioning of women in the face of situations of violence in the narratives in question, in addition to observing the possible tragic outcomes for such abusive relationships.